Foreign Trade and Its Effects on Domestic Economies (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Foreign trade, the exchange of goods and services across international borders, plays a crucial role in shaping the economic landscape of nations. It drives economic growth, enhances consumer choices, and fosters innovation. However, the effects of foreign trade on domestic economies are multifaceted, impacting everything from employment rates to technological advancement. This article explores these impacts in depth, highlighting both the benefits and challenges that come with international commerce.